AIAA Guidance, Navigation, and Control Conference and Exhibit 2001
DOI: 10.2514/6.2001-4273
|View full text |Cite
|
Sign up to set email alerts
|

Integrated orbit, attitude, and structural control system design for space solar power satellites

Abstract: The major objective of this study is to develop an integrated orbit, attitude, and structural control system architecture for very large Space Solar Power Satellites (SSPS) in geosynchronous orbit. This study focuses on the 1.2-GW "Abacus" SSPS concept characterized by a 3.2 × 3.2 km solar-array platform, a 500-m diameter microwave beam transmitting antenna, and a 500 × 700 m earth-tracking reflector. For this baseline Abacus SSPS configuration, we derive and analyze a complete set of mathematical models, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Although the coupling between structural deformation/vibration and attitude motion for long and narrow structures has been investigated extensively [1][2][3], research of planar structures is less common [4]. Furthermore, in the planar structures stabilized by tensile forces, tether slack is a significant problem because the dynamic characteristics of such structures could change drastically when the tension of any of the tethers becomes zero.…”
Section: Introductionmentioning
confidence: 99%
“…Although the coupling between structural deformation/vibration and attitude motion for long and narrow structures has been investigated extensively [1][2][3], research of planar structures is less common [4]. Furthermore, in the planar structures stabilized by tensile forces, tether slack is a significant problem because the dynamic characteristics of such structures could change drastically when the tension of any of the tethers becomes zero.…”
Section: Introductionmentioning
confidence: 99%
“…Wie preliminarily studied the short-term orbital motion with external disturbances and designed a controller for orbit keeping. He also designed a PD controller for the attitude motion with the method of frequency band isolation [7,8]. Ian Mcally put forward an alternative solar power satellite orbital location, known as the geosynchronous Laplace plan (GLP), which is superior to geostationary in many aspects [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The orbit and attitude motions are assumed to be uncoupled [6][7][8][9][10][11][12]. Graf first analyzed the characteristics of the orbital motion of a SPS [6].…”
Section: Introductionmentioning
confidence: 99%
“…1) have been presented [1,2] (summarized in Ref. [3]). It has been reported that many of them have problems in their electrical component, such as transportation of large amounts of electricity over long distances and in the rotation mechanism, and are subject to over-concentration, which makes the power management and distribution systems have the most massive structures [4].…”
Section: Introductionmentioning
confidence: 99%